2011
DOI: 10.1371/journal.pcbi.1002251
|View full text |Cite
|
Sign up to set email alerts
|

High Degree of Heterogeneity in Alzheimer's Disease Progression Patterns

Abstract: There have been several reports on the varying rates of progression among Alzheimer's Disease (AD) patients; however, there has been no quantitative study of the amount of heterogeneity in AD. Obtaining a reliable quantitative measure of AD progression rates and their variances among the patients for each stage of AD is essential for evaluating results of any clinical study. The Global Deterioration Scale (GDS) and Functional Assessment Staging procedure (FAST) characterize seven stages in the course of AD fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
79
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 40 publications
1
79
0
Order By: Relevance
“…Alzheimer's disease (AD) is an heterogeneous neurodegenerative disorder (Schellenberg, 1995;Komarova and Thalhauser, 2011;Lam et al, 2013) that affects Ͼ5 million in the United States alone (Alzheimer's Association, 2015) and is characterized by the progressive accumulation of amyloid ␤ (A␤) and microtubule associated protein tau (Tau), leading to the selective degeneration of neurons in the neocortex, limbic system, and nucleus basalis, among others (Morrison and Hof, 2002;Saxena and Caroni, 2011;Mattsson et al, 2016). In addition to A␤ and Tau, recent studies have shown that ␣-synuclein (␣-syn) (Hansen et al, 1990;McKeith, 2006;Lippa et al, 2007;Larson et al, 2012;Winslow et al, 2014;Walker et al, 2015) and TAR DNA-binding protein (TDP)-43 (Wilson et al, 2011;Colom-Cadena et al, 2013;Borchelt et al, 2014) might also contribute to the pathogenesis of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is an heterogeneous neurodegenerative disorder (Schellenberg, 1995;Komarova and Thalhauser, 2011;Lam et al, 2013) that affects Ͼ5 million in the United States alone (Alzheimer's Association, 2015) and is characterized by the progressive accumulation of amyloid ␤ (A␤) and microtubule associated protein tau (Tau), leading to the selective degeneration of neurons in the neocortex, limbic system, and nucleus basalis, among others (Morrison and Hof, 2002;Saxena and Caroni, 2011;Mattsson et al, 2016). In addition to A␤ and Tau, recent studies have shown that ␣-synuclein (␣-syn) (Hansen et al, 1990;McKeith, 2006;Lippa et al, 2007;Larson et al, 2012;Winslow et al, 2014;Walker et al, 2015) and TAR DNA-binding protein (TDP)-43 (Wilson et al, 2011;Colom-Cadena et al, 2013;Borchelt et al, 2014) might also contribute to the pathogenesis of AD.…”
Section: Introductionmentioning
confidence: 99%
“…The temporal progression of AD exhibits a highly variable pattern among patients and is not fully understood (31). Environmental, age-related, and genetic factors have been proposed to contribute to pathogenesis of the disease.…”
mentioning
confidence: 99%
“…However, there can arise situations for which these assessments fail to adequately capture the disease progression (4). Test–retest reliability, learning effects, floor or ceiling effects, and variability in disease progression (5,6) can confound interpretation of these measures.…”
mentioning
confidence: 99%